Design and Fabrication of Solar and Gasoline Dual-Powered Lawn Mower - Abdulrahman, K. O.; Ibrahim, H. K.; Adeleke, K. K.; Azeez, B. O.; Jamiu, I. A.; Babatunde, R. A.; Abdulazeez, K. O.; Aweda, J. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
The need to improve existing lawnmowers is highly essential, especially when there is availability of alternative and renewable sources of power (solar energy). A readily available two-stroke internal combustion engine and solar panel were used to drive a cutting tool made from a locally available cutlass. The Mechanical power from the internal combustion engine was converted by an alternator to Electrical power and transmitted through the electric motor. The mower’s battery is recharged by a 30W solar panel. To avoid completely draining or overcharging the battery, the solar panels were linked in series with an electric charge controller. The lawn mower’s cutting blade is fixed to a 12-volt, one-horsepower DC motor, which is powered by two series-connected 12-volt, seventy-five-amp lead accumulators. Through the use of solar energy captured by the solar panels, the DC batteries (lead accumulators) are replenished. The hybrid powered lawn’s intricate design was developed and the performance demonstrated the field efficiency of 83% and 87% when powered with solar and combustion engines respectively. The blade height is adjusted for the desired height of the cut. The battery which takes approximately 2 days to recharge mows a total area of 455m2 of lawn. The mower showed neat mowing of the grasses with ease of operation.